Computational thinking in mathematical problem solving: Pattern recognition - Taufik, Marhan; Inam, Akhsanul; Susanti, Reni Dwi (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Computational thinking is increasingly acknowledged as important in education to support the development of problem-solving skills in mathematics. Pattern recognition plays a significant role in solving mathematical problems using computational thinking. This qualitative research explores how students recognize patterns when solving mathematical problems using computational thinking. The study adopts a case study approach, with 46 subjects then chooses two students from the Mathematics Education Study Program selected through purposive sampling. Data collection methods involve tests and interviews in August. The data is qualitatively analyzed, involving reduction, data presentation, and concluding the research findings. The results indicate that the subjects recognized a pattern related to determining the height of a triangle, which was one of the assigned questions. The pattern emerged as the subjects identified the problem, decomposed it, recognized known and unknown information, and identified the relationship between sub-problems and task information. The identified pattern is crucial in addressing the problem in the given task.